Effects of low intensity pulsed ultrasound on expression of B-cell lymphoma-2 and BCL2-Associated X in premature ovarian failure mice induced by 4-vinylcyclohexene diepoxide - Haopeng Xu; Yi Xia; Juan Qin; Jie Xu; Chongyan Li; Yan Wang (BMC, 2021)
Abstract Background Premature ovarian failure (POF) is a common disease in the field of Gynecology. Low intensity pulsed ultrasound (LIPUS) can promote tissue repair and improve function. This study was performed to determine the effects of LIPUS on granulosa cells (GCs) apoptosis and protein expression of B-cell lymphoma-2 (Bcl-2) and BCL2-Associated X (Bax) in 4-vinylcyclohexene diepoxide (VCD)-induced POF mice and investigate the mechanisms of LIPUS on ovarian function and reserve capacity. Methods The current POF mice model was administrated with VCD (160 mg/kg) by intraperitoneal injection for 15 consecutive days. The mice were divided into the POF group, LIPUS group and control group. In the LIPUS group, the right ovary of mice was treated by LIPUS (acoustic intensity was 200 mW/cm2, frequency was 0.3 MHz, and duty cycle was 20%) for 20 min, 15 consecutive days from day 16. The mice of the POF group and control group were treated without ultrasonic output. The basic observation and body weight were recorded. Hematoxylin and eosin staining (H&E staining) and enzyme-linked immunosorbent assay (ELISA) were applied to detect ovarian follicle development, ovarian morphology and sex hormone secretion. Ovarian GCs apoptosis was detected by TUNEL assay and immunohistochemistry. Results The results showed that VCD can induce estrus cycle disorder, follicular atresia, sex hormone secretion decreased and GCs apoptosis in mice to establish POF model successfully. LIPUS significantly promoted follicular development, increased sex hormone secretion, inhibited excessive follicular atresia and GCs apoptosis. The mechanism might be achieved by increasing the protein expression of Bcl-2 and decreasing the expression of Bax in ovaries. Conclusions LIPUS can improve the POF induced by VCD. These findings have the potential to provide novel methodological foundation for the future research, which help treat POF patients in the clinic.